2016
DOI: 10.1007/s00125-016-3933-4
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue plasticity: how fat depots respond differently to pathophysiological cues

Abstract: White adipose tissue (WAT) has key metabolic and endocrine functions and plays a role in regulating energy homeostasis and insulin sensitivity. WAT is characterised by its capacity to adapt and expand in response to surplus energy through processes of adipocyte hypertrophy and/or recruitment and proliferation of precursor cells in combination with vascular and extracellular matrix remodelling. However, in the context of sustained obesity, WAT undergoes fibro-inflammation, which compromises its functionality, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
313
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(328 citation statements)
references
References 120 publications
5
313
1
9
Order By: Relevance
“…In lean humans, subcutaneous adipocytes are larger than visceral adipocytes (Pellegrinelli et al, 2016), whereas the opposite is the case in mice (Sackmann-Sala et al, 2012;Schöttl et al, 2015) (Fig. 2).…”
Section: Metabolic Risk Is Associated With Individual Adipose Tissuementioning
confidence: 92%
“…In lean humans, subcutaneous adipocytes are larger than visceral adipocytes (Pellegrinelli et al, 2016), whereas the opposite is the case in mice (Sackmann-Sala et al, 2012;Schöttl et al, 2015) (Fig. 2).…”
Section: Metabolic Risk Is Associated With Individual Adipose Tissuementioning
confidence: 92%
“…A recent study showed that regulation of lipid storage-related genes (DGAT2, SREBP1c and CIDEA) was defective in the subcutaneous adipose tissue of subjects exhibiting the largest fat accumulation in the visceral adipose tissue of non-obese subjects when overfed for 56 days, supporting the adipose tissue expandability theory (30). Apart from adipogenesis and lipogenesis, appropriate plasticity ensured by remodeling of the extracellular matrix and the vasculature are required for the maintenance of adipose tissue expandability (31).…”
Section: Adipose Tissue Expandabilitymentioning
confidence: 98%
“…We recently assessed in vivo mitochondrial function by 31 P-MRS after energy-depleting exercise in young healthy men born with a low birth weight (LBW) and at increased risk of developing T2D, and since diets high in fat and calories have been linked to mitochondrial dysfunction (89, 90), we investigated the potential effect of 5-day high-fat overfeeding. We found that in vivo mitochondrial function was not affected by overfeeding LBW individuals compared with that in controls (81), thereby not supporting the proposed hypothesis that high-fat diet induces alterations in mitochondrial function -not even in subjects at risk of developing insulin resistance and T2D.…”
Section: Lipid Accumulation In Skeletal Muscle Vs Livermentioning
confidence: 99%
“…WAT generally develops in discrete anatomical depots, identified as subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT); the distribution of fat is closely linked to metabolic disease risk [18, 19]. Emerging evidence has confirmed that the accumulation of VAT is closely related to the metabolic complications of obesity and cardiovascular disease [2023].…”
Section: Introductionmentioning
confidence: 99%